Role of Mean Platelet Volume in Diagnosis of Childhood Acute Appendicitis - Uyanik, Bunyamin; Kavalci, Cemil; Arslan, Engin Deniz; Yilmaz, Fevzi; Aslan, Ozgur; Dede, Serdal; Bakir, Fatih (Emergency Medicine International, 2012)
Introduction. Acute appendicitis is the leading cause of abdominal pain in children requiring emergency surgical intervention. The aim of this study is to investigate the diagnostic value of MPV in early diagnosis of acute appendicitis cases in pediatric age group. Methods. This study was performed retrospectively. Three hundred five patients operated on with the diagnosis of appendicitis and pathologically found to be acute appendicitis were classified as Group 1 and 305 healthy children were classified as control Group 2. Results. One hundred ninety-seven of 305 cases in Group 1 are males (64.6%), in Group 2, 151 of 305 cases are males (49.5%). The mean MPV in Group 1 was 7.9±0.9 (fL), and whereas in Group 2 was 7.7±0.8 (fL). There was no statistically significant difference regarding MPV values (P>0.05). Conclusion. In our study we detected that mean platelet volume has no diagnostic value in pediatric acute appendicitis cases.